Pengembangan Website Edupharmindo Sebagai Media Edukasi Acne Vulgaris - Lolita; Fasyir, Syaima’ Rihan; Puspitasari, Kartini; Triandika, Rifaldy; Nugraheni, Ambar Yunita; Novita, Sisri; Muhlis, Muhammad; Ikhsanudin, Azis; Supadmi, Woro; Nuraisyah, Fatma; Darmawan, Hendra (Jurnal Kesehatan, 2023)
Acne vulgaris is a skin disease caused by excess bacterial activity. This disease is often experienced by young people aged 12-25 years and cause a lack of self-confidence in terms of appearance. The aim of the study is to obtain a web-based educational media in order to provide knowledge and understanding to the public, especially Indonesian students in Nanjing regarding self-medication for acne vulgaris. The research method used to develop the edupharmindo website is the 4-D model. The development stages of “edupharmindo” website are define, design, develop and disseminate. The Edupharmindo website (https://edupharmindo.com/) was disseminated through the social media among Indonesian students in Nanjing under the coordination of Indonesian Students Association, Head of Muhammadiyah and Aisyiyah Special Branch, Nanjing, P.R China. The material contained on this website includes definition, classification, epidemiology, self-medication therapeutic algorithm, aggravating factors of acne vulgaris, etc. The “edupharmindo” website feasibility was assessed by material experts, media experts and Indonesian students. The data were analyzed descriptively and quantitatively. The results showed that “edupharmindo” website was in the "very feasible" in category (technical operations, material accuracy, up-to-date references, presentation techniques, and material presentation support) and feasible in category (appearance, language, colour, illustrations, communicative). Therefore, this website should be applied as an educational media for acne vulgaris.